Structure and Physical Properties of In2Se3, InSe and InSe<Fe> Layered Crystals - Kaminskii, V. M.; Kovalyuk , Z. D.; Ivanov, V. I. (Physics and Chemistry of Solid State, 2015)
The influence of magnetic impurities on the properties of In2Se3 and InSе layered crystals was studied. The results indicate the formation of substitutional solid solutions in the In2Se3<1 wt. % Mn>, InSe<0.5 wt. % Mn> single crystals. Temperature dependences of electroconductivity across (σ^С) and along (σ||С) the С crystallographic axis of doped crystals were measured in the range of 80–400 K. The values of energy barrier height between the crystal layers ΔЕδ were evaluated for In2Se3 and InSe. It was established that InSe<Fe> crystals exhibit ferromagnetic properties.